The super leadership behavior of school administrators Affecting the professional learning communiity of School under the secoundary educatioanl Service area offoce Nongkhai - Seeprasom, Pilaiwan; Choeybal, Panayuth (Journal for Developing the Social and Community, 2023)
The purposes of this research were to 1) study the components and indicators of the super leadership behavior of school administrators, 2) study super leadership behavior of school administrators, 3) study the professional learning community of schools, 4) study the leadership between super leadership of school administrators and the professional learning community of schools, and 5) create a forecast of the schools professional learning community under the Secondary Educational Service Area Office Nongkhai. In the research was conducted associated with 2 phases. The first phase was was to investigate the component of the super leadership behavior of school administrators. The best practice was studied out of 3 school administrators who were selected purposively for the in-depth interviewing. There were 5 experts verify the components. The instruments were unstructured interview form and component verified form. Content analysis and percentage were used in data analysis. The second phase was to study the super leadership behavior of school administrators. The samples were 285 teachers in the school under the Secondary Educational Service Area Office Nongkhai using stratified random sampling. The instrument was a 5 rating-scales questionnaire with the reliability of .987 and .986 respectively. The statistics used for data analysis were frequency distribution, percentage, mean and standard deviation, Pearson's product moment correlation coefficient, and stepwise multiple regression analysis. The results of the research showed that 1) The components of the Super leadership behavior of school administrators had 5 components and 50 indicators. 2) The Super leadership behavior, school administrators under the Secondary Educational Service Area Office Nongkhai, was at in the high level. 3) The Professional Learning Community of schools under the Secondary Educational Service Area Office Nongkhai, was at in the high level. 4) The Super leadership of school administrators and the professional learning community of schools under the Secondary Educational Service Area Office Nongkhai, they had a relationship. 5) The forecasting equation for the professional learning community of schools under the Secondary Educational Service Area Office Nongkhai, by using super leadership of school administrators as predictive variable 71.20 percent power, with the following equation. The forecasting equation in raw scores as follows equation of raw score: = .827+.379(X5)+.243(X1)+.174(X3). The equation of standard score: = .452(X5)+.273(X1)+.188(X3) The purposes of this research were to 1) study the components and indicators of the super leadership behavior of school administrators, 2) study super leadership behavior of school administrators, 3) study the professional learning community of schools, 4) study the leadership between super leadership of school administrators and the professional learning community of schools, and 5) create a forecast of the schools professional learning community under the Secondary Educational Service Area Office Nongkhai. In the research was conducted associated with 2 phases. The first phase was was to investigate the component of the super leadership behavior of school administrators. The best practice was studied out of 3 school administrators who were selected purposively for the in-depth interviewing. There were 5 experts verify the components. The instruments were unstructured interview form and component verified form. Content analysis and percentage were used in data analysis. The second phase was to study the super leadership behavior of school administrators. The samples were 285 teachers in the school under the Secondary Educational Service Area Office Nongkhai using stratified random sampling. The instrument was a 5 rating-scales questionnaire with the reliability of .987 and .986 respectively. The statistics used for data analysis were frequency distribution, percentage, mean and standard deviation, Pearson's product moment correlation coefficient, and stepwise multiple regression analysis. The results of the research showed that 1) The components of the Super leadership behavior of school administrators had 5 components and 50 indicators. 2) The Super leadership behavior, school administrators under the Secondary Educational Service Area Office Nongkhai, was at in the high level. 3) The Professional Learning Community of schools under the Secondary Educational Service Area Office Nongkhai, was at in the high level. 4) The Super leadership of school administrators and the professional learning community of schools under the Secondary Educational Service Area Office Nongkhai, they had a relationship. 5) The forecasting equation for the professional learning community of schools under the Secondary Educational Service Area Office Nongkhai, by using super leadership of school administrators as predictive variable 71.20 percent power, with the following equation. The forecasting equation in raw scores as follows equation of raw score: = .827+.379(X5)+.243(X1)+.174(X3). The equation of standard score: = .452(X5)+.273(X1)+.188(X3)